Implementasi Perlindungan Merek Terkenal: Analisis Kasus Ikea dan Sephora di Era Globalisasi - Muammar Habibi, Nauval (Syntax Corporation, 2025)
Legal protection of popular brands in Indonesia is an important aspect of maintaining brand reputation and integrity in a competitive market. This article examines the application of legal protection to two popular brands, namely IKEA and Sephora, with emphasis on the legal challenges they face and the procedures for resolving concurrency. Through an analysis of the IKEA case, which involved a summons regarding trademark use, and the Sephora case which highlighted the importance of brand reputation protection, this article argues that Law Number 20 of 2016 concerning Trademarks and Geographical Indications provides a strong legal basis for protecting popular brands. The legal decisions taken in these two cases demonstrate that brand reputation and recognition are primary considerations in legal protection. This article also recommends increasing legal awareness among brand owners, consumer education, and cooperation with the government to build a more conducive and fair environment for all parties involved. Thus, legal protection of popular brands is not only beneficial for brand owners, but also contributes to market stability and consumer protection.